2020
DOI: 10.4236/jss.2020.81009
|View full text |Cite
|
Sign up to set email alerts
|

Belt and Road Initiative (BRI) of China: Connecting the World for Sustainable Economic Development

Abstract: The aim of this article is to assess the effect of strategies of Belt and Road Initiative (BRI) on sustainable economic development of member countries. This study is based on qualitative approach and secondary data. A number of documents such as journal articles, government reports, books, book chapters and working papers have been consulted to substantiate the arguments. The article explores that there is a potential effect of BRI on the sustainable economic development of its member countries. Some of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…He noted both its importance for the Middle Kingdom's international position as well as emphasised economic desirability for the less developed countries that would experience rapid growth of their industries. Rasel et al (2020) performed a literature review, covering 97 papers, addressing the OBOR initiative from various perspectives. The review concluded the study with the message that each member country should devote all available political and economic resources to support this initiative as despite direct profits all the members would gain diverse benefits for the infrastructure development, trading, bilateral agreements, etc.…”
Section: Obor Initiativementioning
confidence: 99%
“…He noted both its importance for the Middle Kingdom's international position as well as emphasised economic desirability for the less developed countries that would experience rapid growth of their industries. Rasel et al (2020) performed a literature review, covering 97 papers, addressing the OBOR initiative from various perspectives. The review concluded the study with the message that each member country should devote all available political and economic resources to support this initiative as despite direct profits all the members would gain diverse benefits for the infrastructure development, trading, bilateral agreements, etc.…”
Section: Obor Initiativementioning
confidence: 99%
“…Asia will be going to emerge as the centre of intra-regional economies under the dynamics of the evolving worldwide commercial and trading order, whereas countries of the Middle Eastern region have become a significant source of fuel (Rasel et al, 2020). The area of the Persian Gulf remains the oil industry's "economic centre of gravity," encompassing the largest oilfields of the world, the lowest production rates, and about two-thirds of the proven global reserves of energy (Manochehr & James, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The era of Mao Zedong has been considered significant during which the foundations of China's growing energy consumption were laid, and the oil industry of China was shaped (Sharma, 2019). With the continuation of China and the Middle East deepening relations concerning energy supplies, efforts for extension and strengthening diplomatic links with the Middle East countries were also made in the past (Rasel et al, 2020). Mao was passionate about developing the country's oil resources to become self-sufficient (Michal, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation